Long-term outcomes of cardiac resynchronization therapy and implantable cardioverter defibrillators in elderly patients with heart failure - Yanxiao Su; Zonglei Wu; Chao Luan; Feifei Chen; Fenglan Huang; Jinqiu Liu (BMC Cardiovascular Disorders)
Abstract Aims We aimed to describe the safety and efficacy of cardiac resynchronization therapy (CRT) and implantable cardioverter defibrillators (ICDs) in elderly patients with heart failure. Methods and results Patients with heart failure who received CRT or ICDs implantation for the first time from 2010 to 2021 were retrospectively studied. 48 of the 115 patients (41.7%) who underwent CRT implantation and 61 of the 174 patients (35.1%) who underwent ICDs implantation were ≥ 70 years old; these patients were defined as “elderly”. The incidence of procedure-related complications was did not differ between elderly and young patients. The median follow-up times of the CRT group and ICDs group were 45 (30,74) and 51 (30,79) months, respectively. There was no significant difference in the superresponse rate, response rate, heart failure readmission rate, all-cause death rate, or cardiac death rate between elderly and young patients. The largest changes in LVEF and LVEDD occurred at 3 years after implantation, and the effect of reversing left ventricular remodeling lasted for five years after implantation. In the ICDs group, no significant difference was observed in the correct discharge ratio between elderly and young patients. However, elderly patients exhibited a significantly higher all-cause mortality rate compared to their younger counterparts (31% vs. 18%, P = 0.035). The survival curves diverged after 5 years, yet no statistically significant difference was found in cardiac death rates between the two groups (16% vs. 14%, P = 0.522). The COX regression model suggested that age ≥ 70 years old and chronic kidney disease were independent risk factors for all-cause death (HR = 1.963, 3.165, P = 0.041, 0.003), while LVEF ≤ 20% was an independent risk factor for cardiac death (HR = 3.562, P = 0.004). Conclusion Implantation of CRT and ICDs in elderly patients with heart failure is safe. Age should not be a criterion for preventing CRT implantation. The prognosis of ICDs implantation in elderly patients is strongly affected by noncardiogenic factors, and the long-term benefit is worse than that in young patients.